Phosphorus released by native bacteria from Riecito (Falcon State) and Navay (Táchira State) phosphate rocks in Venezuela (Bioagro, 2025)
Phosphorus (P) deficiency in acid soils in Venezuela is frequent, to achieve good crop production farmers applied high-cost phosphate fertilizers. The use of phosphate rock as a source of P is an alternative, but it has low solubility and slow release of available P. The objective of this work was to identify bacteria capable to solubilizing Riecito and Navay phosphate rocks and release P. A total of 26 strains collected in different places in the country were used to find out the amount of P released into the medium by the action of the strains, and 14 of which were used to measure bacterial growth at different times, according their optical density. An in vitro experiment was carried out using 100 µL of concentrated bacterial suspension in 10 mL of NBRIP culture medium under sterile conditions. The sources of P were: tricalcium phosphate (FTC), Navay phosphate rock (RFN)) and Riecito phosphate rock (RFR) and 0P, plus the non-inoculated controls. The highest values of P, in µg.mL-1 corresponded to the FTC with 320 to 500 followed by RFN with 133 to 210 and RFR between 62 and 73. Strains G166, La37-26 and Ar146 showed the lowest pH levels in the growth media enriched with RFN and RFR and corresponded to the highest levels of solubilized phosphorus. This behavior demonstrates that bacteria with higher acidification capacity are potentially more effective in solubilizing unavailable P from phosphate rocks.
Keywords: Bacterial growth; optical density; phosphorus release